Development and Characterization of Graphene Nanoplatelets Reinforced Aluminum Nanocomposites - BAIG, ZEESHAN (2018)
Light weight of the materials and their high mechanical performances are the special needs of the automotive industries for cost effectiveness and fuel economy.